Helicobacter pylori VacA, acting through receptor protein tyrosine phosphatase α, is crucial for CagA phosphorylation in human duodenum carcinoma cell line AZ-521 - Masayuki Nakano; Kinnosuke Yahiro; Eiki Yamasaki; Hisao Kurazono; Junko Akada; Yoshio Yamaoka; Takuro Niidome; Masanori Hatakeyama; Hidekazu Suzuki; Taro Yamamoto; Joel Moss; Hajime Isomoto; et al. (The Company of Biologists, 2016)
Helicobacter pylori, a major cause of gastroduodenal diseases, produces vacuolating cytotoxin (VacA) and cytotoxin-associated gene A (CagA), which seem to be involved in virulence. VacA exhibits pleiotropic actions in gastroduodenal disorders via its specific receptors. Recently, we found that VacA induced the phosphorylation of cellular Src kinase (Src) at Tyr418 in AZ-521 cells. Silencing of receptor protein tyrosine phosphatase (RPTP)α, a VacA receptor, reduced VacA-induced Src phosphorylation. Src is responsible for tyrosine phosphorylation of CagA at its Glu-Pro-Ile-Tyr-Ala (EPIYA) variant C (EPIYA-C) motif in Helicobacter pylori-infected gastric epithelial cells, resulting in binding of CagA to SHP-2 phosphatase. Challenging AZ-521 cells with wild-type H. pylori induced phosphorylation of CagA, but this did not occur when challenged with a vacA gene-disrupted mutant strain. CagA phosphorylation was observed in cells infected with a vacA gene-disrupted mutant strain after addition of purified VacA, suggesting that VacA is required for H. pylori-induced CagA phosphorylation. Following siRNA-mediated RPTPα knockdown in AZ-521 cells, infection with wild-type H. pylori and treatment with VacA did not induce CagA phosphorylation. Taken together, these results support our conclusion that VacA mediates CagA phosphorylation through RPTPα in AZ-521 cells. These data indicate the possibility that Src phosphorylation induced by VacA is mediated through RPTPα, resulting in activation of Src, leading to CagA phosphorylation at Tyr972 in AZ-521 cells.